The integration of signaling and the spatial organization of the T cell synapse - Rossy, Jeremie; Williamson, David J.; Benzing, Carola; Gaus, Katharina (Frontiers in Immunology, 2012)
Engagement of the T cell antigen receptor (TCR) triggers signalling pathways that lead to T cell selection, differentiation and clonal expansion. Superimposed onto the biochemical network is a spatial organization that describes individual receptor molecules, dimers, oligomers and higher order structures. Here we review recent finding about TCR organization in naïve and memory T cells. A key question that has emerged is how antigen-TCR interactions encode spatial information to direct T cell activation and differentiation. Single molecule super-resolution microscopy may become an important tool in decoding receptor organization at the molecular level.